New Sensation. Issue 1 (7th January 2021) - Bebensee, Fabian; Welter, Kira; Heydenrych, Greta
Abstract : New Sensation : ChemPhysChem has been going strong for just over 20 years now. On April 1 2020, we took on a modern new look, abandoning the blue framed cover that was an integral part of ChemPhysChem 's identity, together with our whole Chemistry Europe journal family.